2020
DOI: 10.3389/fpsyt.2020.00564
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody Biomarkers for Basal Ganglia Encephalitis in Sydenham Chorea and Pediatric Autoimmune Neuropsychiatric Disorder Associated With Streptococcal Infections

Abstract: sera of PANDAS subjects, who had 76-89% positive association with elevated individual autoantibody titers and positive CaMKII activity. At 6 months follow-up, symptoms improved for more than 80% of PANDAS subjects, and serum autoantibody titers also significantly decreased. Results reported herein and previously published studies in our laboratory suggest the antibody biomarkers may be a useful adjunct to clinical diagnosis of SC, PANDAS, and related disorders and are the first known group of autoantibodies de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 80 publications
4
53
0
1
Order By: Relevance
“…The results of a recent study revealed an increase in anti-neuronal autoantibody titers and the activity of CaMKII pathway in human neuronal cells in the acute phase of PANDAS ( 17 ). The autoantibody titers decreased during improvement.…”
Section: Resultsmentioning
confidence: 99%
“…The results of a recent study revealed an increase in anti-neuronal autoantibody titers and the activity of CaMKII pathway in human neuronal cells in the acute phase of PANDAS ( 17 ). The autoantibody titers decreased during improvement.…”
Section: Resultsmentioning
confidence: 99%
“…Because this patient had concurrent infections, we have referred to this case as a patient with PANDAS and Lyme co-infection. We suggest that the utilization of the term “Basal Ganglia Encephalitis (BGE)” may have more clinical utility when referring to the possible pathophysiology, where the type of infectious trigger may not be essential in the nomenclature of the clinical syndrome ( 26 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…SC and PANDAS may share an underlying pathogenesis. Accumulating evidence shows that autoantibodies target antigens in the basal ganglia of these patients [ 84 , 85 , 86 , 87 , 88 ]. Through the molecular mimicry process, autoantibodies against N-acetyl-beta-D-glucosamine (GlcNAc), the dominant epitope of the GAS carbohydrate, cross-react with neuronal antigens, leading to neurological symptoms [ 85 , 89 ].…”
Section: Immune Dysregulation In Tsmentioning
confidence: 99%
“…Through the molecular mimicry process, autoantibodies against N-acetyl-beta-D-glucosamine (GlcNAc), the dominant epitope of the GAS carbohydrate, cross-react with neuronal antigens, leading to neurological symptoms [ 85 , 89 ]. Cross-reacting neuronal antigens include lysoganglioside-GM1 and beta-tubulin, both of which immunologically mimic GLcNAc [ 84 , 85 , 86 ]. They further induced CaMKII kinase activation [ 84 , 85 ].…”
Section: Immune Dysregulation In Tsmentioning
confidence: 99%
See 1 more Smart Citation